The genome sequence of a cave beetle, Leptodirus hochenwartii F.J.Schmidt, 1832 [version 1; peer review: 2 approved] - Teo Delić (Wellcome Open Research)
We present a genome assembly from a male specimen of Leptodirus hochenwartii (cave beetle; Arthropoda; Insecta; Coleoptera; Leiodidae). The genome sequence has a total length of 492.36 megabases. Most of the assembly (98.03%) is scaffolded into 14 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 22.01 kilobases in length.